Identification of anthocyanins in the fruits of Kadsura coccinea using UPLC-MS/MS-based metabolomics. (October 2021) - Huang, Ding; Ming, Ruhong; Yao, Shaochang; Li, Liangbo; Huang, Rongshao; Tan, Yong
Abstract: Fruit color is thought to be an adaptation to different animal pollinators, the fruits of Kadsura coccinea present diverse colors but the metabolic mechanism of the differences in color still needs further clarification. Here, we performed ultra-performance liquid chromatography-tandem mass spectrometry based on targeted metabolome analysis of the fruits of two K. coccinea cultivars, 'Dahong No. 1' (red-peel) and 'Jinhu' (yellow-peel). A total of seventeen anthocyanins were identified in the fruit peels of 'Dahong No. 1', whereas no anthocyanins were detected in 'Jinhu'. Our results suggest that the color differences between the two cultivars can be explained by variations in abundance of cyanidin 3-O-rutinoside, cyanidin 3-O-glucoside and delphinidin 3-O-glucoside, accounting for 91.64% of the content of total anthocyanins. This study provides new insights into the underlying metabolic causes of color variation in K. coccinea fruits, and thus provides a theoretical basis for the development and utilization of K. coccinea fruits in the future. Highlights: A total of 17 kinds of anthocyanin were identified from the fruits of two K. coccinea cultivars. The 17 identified anthocyanins were differentially accumulated between two cultivars. Cyanidin 3-O-rutinoside, cyanidin 3-O-glucoside and delphinidin 3-O-glucoside provide red color of 'Dahong No. 1' cultivar. Results provide new insights about metabolic causes of color variation in K. coccinea.